Outcome for Patients with Triple-Negative Breast Cancer Is Not Dependent on Race/Ethnicity - Quyen D. Chu; Amanda E. Henderson; Fred Ampil; Benjamin D. L. Li (International Journal of Breast Cancer)
Introduction. Triple negative breast cancer (TNBC) is biologically aggressive and is associated with a worse prognosis. To understand the impact of race/ethnicity on outcome for patients with TNBC, confounding factors such as socioeconomic status (SES) need to be controlled. We examined the impact of race/ethnicity on a cohort of patients of low SES who have TNBC. Methods. 786 patients with Stage 0–III breast cancer were evaluated. Of these, 202 patients had TNBC (26%). Primary endpoints were cancer recurrence and death. ZIP code-based income tract and institutional financial data were used to assess SES. Data were analyzed using Kaplan-Meier survival analysis, log-rank tests, Cox Proportional hazard regression, chi square test, and t-tests. A P value ≤0.05 was considered statistically significant. Results. Of the 468 African-Americans (60%) in the database, 138 had TNBC; 64 of 318 Caucasians had TNBC. 80% of patients had an annual income of ≤$20,000. The 5-year overall survival was 77% for African-American women versus 72% for Caucasian women (𝑃=0.95). On multivariate analysis, race/ethnicity had an impact on disease-free survival (𝑃=0.027) but not on overall survival (𝑃=0.98). Conclusion. In a predominantly indigent population, race/ethnicity had no impact on overall survival for patients with triple negative breast cancer.